PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KLOFFEE KOPI JAGAKARSA - Moch. Bani Khoerul Abdullah; Ahmad Dimyati (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of price and promotion on purchasing decisions for Kloffee Kopi Jagakarsa. The research method used is a quantitative descriptive method. The sampling technique used is a probability sampling technique in the form of simple random sampling. The sampling technique uses the Slovin formula with a tolerable error limit of 10%, so that a sample of 91 respondents is obtained. Data analysis methods include validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the research show that price has a positive and partially significant effect on purchasing decisions with a coefficient of determination value of 66.2%, and the hypothesis test obtained t count > t table (13.194 > 1.987) or a significance of 0.000 < 0.05. Promotion also has a positive and partially significant effect on purchasing decisions with a coefficient of determination value of 73.6% and hypothesis test t count > t table (15.764 > 1.987) or significance of 0.000 < 0.05. Price and promotion simultaneously have a significant effect on purchasing decisions with the regression equation Y = 2.187 + 0.249 X1 + 0.693 X2. The coefficient of determination value is 74.9%, while the remaining 25.1% is influenced by other factors. Hypothesis testing shows the calculated F value > F table (131.102 >3.100).